2018
DOI: 10.1039/c8ta08249a
|View full text |Cite
|
Sign up to set email alerts
|

Laser-reduced graphene-oxide/ferrocene: a 3-D redox-active composite for supercapacitor electrodes

Abstract: Supercapacitors are energy storage and conversion devices that display high power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 36 publications
1
35
0
1
Order By: Relevance
“…Detailed structural characterization and reaction mechanisms of the laser-reduction process of GO or CNDs have been published previously. 22,23,26,27 In all our experiments the same laser power was used, and it was found that the investigated samples react differently upon laser impact. The precursor films with higher CND mass fractions are more stable against laser-induced evaporation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed structural characterization and reaction mechanisms of the laser-reduction process of GO or CNDs have been published previously. 22,23,26,27 In all our experiments the same laser power was used, and it was found that the investigated samples react differently upon laser impact. The precursor films with higher CND mass fractions are more stable against laser-induced evaporation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1. [23][24][25][26] To ensure equal mass loading throughout the samples on the substrates prior to the laser-reduction step, the amount of applied solution was adjusted accordingly (Table 1). Solutions were either prepared in H 2 O or in a 1 : 1 mixture of N-methyl-2pyrrolidone (NMP) and iso-propanol (i-PrOH) (NMP/i-PrOH (1 : 1 v/v)) to produce uniform films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The de‐oxidation process separated the graphene sheets, so they were exposed rather than being stacked one on top of the other. The product of this method was thoroughly studied in previous papers . Some of these data including a few physical properties of the product, are presented in the Supporting Information in Table S1 and Figure S1.…”
Section: Introductionmentioning
confidence: 99%